The Be-test in the Li-rich star #1657 of NGC 6397: evidence for Li-flash in RGB stars? - Pasquini, Luca; Koch-Hansen, Andreas; Smiljanic, Rodolfo; Bonifacio, Piercarlo; Modigliani, A. (Astronomy and astrophysics, 2014)
Context. The Li-rich turn-off star recently discovered in the old, metal-poor globular cluster NGC 6397 could represent the smoking gun for some fundamental, but very rare episode of Li enrichment in globular clusters and in the early Galaxy. Aims. We aim to understand the nature of the Li enrichment by performing a spectroscopic analysis of the star, in particular of its beryllium (Be) abundance, and by investigating its binary nature.Methods. We used the VLT/UVES spectrograph to observe the near UV region where the Be ii resonance doublet and the NH bands are located. We also re-analyzed an archival Magellan/MIKE spectra for C and O abundance determination. Results. We could not detect the Be ii lines and derive an upper limit of log (Be/H) < −12.2 that is consistent with the Be observed in other stars of the cluster. We could detect a weak G-band, which implies a mild carbon enhancement [C/Fe]+ 0.4 ± 0.2. We could not detect the UV NH band, showing that this star is less N-enhanced than other stars of the cluster, and we derive an upper limit [N/Fe] < 0.0. For oxygen we could not convincingly detect any of the near UV OH lines, which implies that oxygen cannot be strongly enhanced in this star. This is consistent with the detection of the strongest line of the O i triplet at 777 nm, which is contaminated by telluric absorptions but is consistent with [O/Fe] ~ 0.5. Combining the UVES and Mike data, we could not detect any variation in the radial velocity greater than 0.95 kms-1 over 8 years.Conclusions. The chemical composition of the star strongly resembles that of “first generation” NGC 6397 stars, with the huge Li as the only deviating abundance. Not detecting Be rules out two possible explanations of the Li overabundance: capture of a substellar body and spallation caused by a nearby type II SNe. Discrepancies are also found with respect to other accretion scenarios, except for contamination by the ejecta of a star that has undergone the RGB Li-flash. This is at present the most likely possibility for explaining the extraordinary Li enrichment of this star.
Gesehen am 13.08.2020